Pulsed laser ablation of silver: ion dynamics in plasma plume - LUNNEY, JAMES; DONNELLY, TONY (My University, 2010)
The ion dynamics of silver ablated using 355 and 193nm pulsed laser irradiation in vacuum has been investigated by using a Langmuir probe and quadrupole mass spectrometry. The kinetic energies of the ablated silver ions were measured to be between 5 and 40 eV depending on the laser fluence. In addition, the angular distributions of ablated species showed that ionic species are preferentially ejected along the surface normal and the corresponding plasma temperature T ? 0.7 eV agrees well for both techniques.
Journal of Optoelectronics and Advanced Materials
PUBLISHED
Keywords: Atomic, molecular and chemical physics; Nanoscience & Materials